DETECTION OF VIRULENCE AND ADHERENCE GENE IN Escherichia Coli O157:H7 ISOLATED FROM ANIMAL PRODUCTS - Basil A. Abbas (Basrah Journal of Veterinary Research)
Twenty nine E. coli isolates were previously isolated from beef from slaughter house, and raw milk of different origin were collected from different parts in Basrah. Five E. coli isolates were identified as E.coli O157:H7 using O157 and H7 antisera. E. coli O157:H7 isolates were tested for antimicrobial susceptibility test. The results showed that all tested bacteria were sensitive to gentamycin and Amikacin and resistant to amoxicillin and cefoxitim. The DNA of these isolates were amplified to detect verotoxins gene (vt1, 91bp) and pyelonephritis-associated pili gene ( pap,91bp). All the isolates were observed having (vt1) All the isolates were observed having (vt1) and pap genes.